Coping with diabetes - Kelly, Pat. (New York : Rosen Pub. Group, 1998)
Discusses the types and causes of diabetes, how the disease is diagnosed and treated, and ways of managing this condition and its impact on your life.
Includes bibliographical references (p. 140) and index.
Keywords: Diabetes -- Juvenile literature; Diabetes in children -- Juvenile literature; Diseases